Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan Menulis Teks Prosedur pada Siswa Kelas XI SMK Swasta Jambi Medan - Siti Fatimah Zahara (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
One of the writing activities contained in learning Indonesian at SMK 2013 curriculum is writing procedure text. The selection of the problem based learning model in this study was based on the idea that the problem based learning model could stimulate students' enthusiasm to be actively involved in their learning experience. The problem-based learning model requires students to think, understand and find the steps that must be taken correctly in writing procedure texts. The results of the research that have been explained that between X1 and X2 obtained from the work of students writing procedural texts from class XI-1, totaling 35 students, obtained a satisfactory assessment or there was an influence that occurred in the learning process. In the learning process at the first meeting, students still used the lecture method with a total score of 2,354 while using the problem based learning model, the students got an overall score of 2,842, in this case there were differences in the process or results in learning to write students' explanatory texts. After getting the overall results, as explained in the description of the research results and hypothesis testing using the steps or formulas used and obtaining the overall value, n = 35 and = 0.05, then the t = 1.692 value is obtained. Because tcount > t table or 33.54 > 1.692 then Ho is rejected. These results provide an explanation that in using the problem based learning learning model there is an influence in the applied learning.